High-strength 99 aluminum oxide ceramic as well as preparation method and application thereof
By using boehmite and hydrotalcite composite sol as binder, the problem of improving the bending strength and density of alumina ceramics is solved, the problem of high-temperature decomposition of traditional binders is avoided, and the preparation of high-strength and high-density alumina ceramics is achieved.
Patent Information
- Application Number
- CN202411763076.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, there is still room for improvement in the bending strength and density of alumina ceramics, and the decomposition of traditional binders under high temperature conditions leads to pores and cracks.
Boehmite and hydrotalc are used as the main components of the binder to obtain boehmite-hydrtalc composite sol through a specific preparation method, which is used in the preparation process of alumina ceramics. The method includes mixing and grinding of boehmite and hydrotalcite, adding a dispersant and a nitric acid solution to prepare a binder, then mixing with alumina and sintering additives, ball milling and sieving to form a powder, and finally producing a high-strength 99 alumina ceramic by pressing and sintering.
Through this method, pores and cracks caused by high temperature decomposition of traditional binders are avoided, the density and hardness of alumina ceramics are improved, and its bending strength and dielectric properties are enhanced.
Smart Images

Figure BDA0005168174990000071 
Figure BDA0005168174990000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alumina ceramics, and in particular relates to a high-strength 99 alumina ceramic and a preparation method and application thereof. Background Art
[0002] 99 alumina ceramics, also known as alumina 99 porcelain, refer to advanced engineering ceramics with an alumina content of more than 99% and α-alumina as the main crystal phase, including 99.5% alumina ceramics, 99.6% alumina ceramics, 99.8% alumina ceramics, etc. Alumina has a variety of isomorphous crystals, α-alumina, β-alumina, and γ-alumina are more common, among which α-alumina has a compact crystal structure, the highest stability, and high industrial application value. In ceramic products, the purity and application ratio of alumina affect its electrical properties, mechanical properties, etc. The higher the purity of alumina ceramics, the higher the dielectric constant and the lower the dielectric loss, but its processing cost and complexity also increase accordingly.
[0003] The strength, dielectric and insulation properties of alumina ceramics are affected by many factors, and the preparation process is an important factor affecting the flexural strength of alumina ceramics. Molding pressure, temperature control and sintering conditions will affect the microstructure and properties of the material. For example, too high molding pressure may cause cracks inside the material, thereby reducing the flexural strength; improper control of sintering temperature and time may cause the grain size of the material to be too large or too small, which is also not conducive to the improvement of flexural strength. In addition, the microstructure of alumina ceramics also has an important influence on the dielectric and insulation properties. The microscopic characteristics of the material such as grain size, distribution and phase interface will affect the performance of its mechanical properties. By optimizing the preparation process, the microstructure of the material can be controlled, thereby improving its flexural strength, dielectric and insulation properties. The prior art CN117923887A discloses a production process for high-hardness alumina ceramics. By using yttrium oxide-modified polyvinyl alcohol as an alumina ceramic binder, its bonding properties are greatly improved compared to polyvinyl alcohol. Adding it into the system as a binder can reduce the amount of binder used, thereby reducing the holes and cracks formed during the debinding process, and helping to improve the density during the sintering process. However, the amount of polyvinyl alcohol added in the prior art is relatively large, and yttrium oxide has limited effects on the density and strength of alumina ceramics. Therefore, it is necessary to provide a method for preparing high-strength alumina ceramics. Summary of the invention
[0004] In order to improve the strength of 99 alumina ceramics, the present invention provides a method for preparing high-strength 99 alumina ceramics. By using boehmite and hydrotalcite as the main components of the binder, a specific preparation method is adopted to obtain the boehmite and hydrotalcite composite sol of the present invention, which is used in the preparation process of alumina ceramics to obtain high-strength and high-density alumina ceramic materials.
[0005] One object of the present invention is to provide a high-strength 99 alumina ceramic, characterized in that it comprises the following components by mass percentage: 99.5-99.8% alumina, 0.05-0.1% sintering aid, and the remainder being boehmite-hydrotalcite composite sol.
[0006] Furthermore, the purity of the aluminum oxide is ≥99.99%, and D50=0.3 μm.
[0007] Furthermore, the sintering aid is one of Cr2O3 and Y2O3, and the particle size is 180-200nm.
[0008] Furthermore, the boehmite-hydrotalcite composite sol is prepared by the following method:
[0009] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:0.5-2, and ground to a particle size of 60-100 nm to obtain a nano powder mixture.
[0010] S2: adding the ground nano powder mixture into a dispersant and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nano powder mixture to the dispersant is 10:0.1-0.5.
[0011] S3: slowly adding a nitric acid solution with a pH value of 2-3 to the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.5-1 mL:5 g, to obtain the binder of the present invention.
[0012] Furthermore, in step S1, the particle size of boehmite and hydrotalcite before grinding is 180-200 nm.
[0013] Furthermore, the dispersant in step S2 is polyvinyl alcohol.
[0014] Another object of the present invention is to provide a method for preparing high-strength 99 alumina ceramics, which is characterized by comprising the following steps:
[0015] Step 1: Weigh alumina and sintering aid according to the above ratio, mix to obtain a mixture; ball mill, and sieve to obtain powder.
[0016] Step 2: Add the powder obtained in step 1 to a boehmite-hydrotalcite mixed sol as a binder to form granules, and place the granules into a molding mold for pressing to obtain a green body.
[0017] Step 3: Place the green body obtained in step 2 into a sintering furnace for debinding at 600-750°C for 3 hours, and then sinter at 1380-1450°C in an atmosphere for 4-8 hours to produce 99 alumina ceramics.
[0018] Further, the specific conditions of the ball milling in step 1 are: adding the mixture: zirconium oxide balls: deionized water in a mass ratio of 1:4:1 into a ball mill, mixing with a planetary ball mill for 3-6 hours, drying at 80-100° C. after taking out, and sieving with a 40-80 mesh sieve to obtain a powder;
[0019] Furthermore, the pressing pressure in step 2 is 10-30 MPa.
[0020] Another object of the present invention is to provide an application of high-strength 99 alumina ceramics in high-frequency insulating materials.
[0021] The present invention has the following beneficial effects:
[0022] The present invention uses boehmite and hydrotalcite as the main components of the binder, and prepares the boehmite-hydrotalcite composite sol by a specific method. The composite sol is used for alumina ceramics, avoiding the pores and cracks caused by the high-temperature decomposition of traditional binders, and improving the density and hardness of the ceramics. The hydrotalcite decomposes during the molding process to form magnesium aluminum spinel and periclase, which refines the Al2O3 grains, reduces the pores, and improves the density, thereby enhancing the hardness and dielectric properties. MgO replaces Al 3+ Point defects are formed, mass transfer is promoted, the grain growth rate and densification rate are increased, abnormal grain growth is inhibited, and the structure is homogenized. MgO can also reduce the sintering temperature of alumina, reduce the calcination temperature, and obtain a high-density product. In addition, the MgO decomposed in the binder used in the present invention can react with the sintering aid Y2O3 and Al2O3 to generate a low-melting-point liquid phase, which helps to redistribute the material between the particles and fill the pores, further improve the density and enhance the dielectric properties. DETAILED DESCRIPTION
[0023] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.
[0024] Example 1
[0025] According to weight percentage, 99.5% of alumina (purity ≥ 99.99%, D50 = 0.3 μm) and 0.05% of sintering aid (Y2O3, particle size 180 nm) are weighed and prepared to obtain a mixture; the mixture: zirconium oxide ball: deionized water are added into a nylon ball mill according to the mass ratio of 1:4:1, and the mixture is mixed by planetary ball milling for 6 hours. After being taken out, the mixture is dried at 80°C and sieved with a 40-80 mesh sieve to obtain a powder; the obtained powder is added into a boehmite-hydrotalcite composite sol for granulation, the granules are placed into a molding mold and a green body is obtained at a pressure of 30 MPa; the obtained green body is placed into a sintering furnace for debinding at 650°C for 3 hours, and then sintered in an atmosphere at 1450°C for 6 hours to obtain 99 alumina ceramics.
[0026] In this embodiment, the boehmite-hydrotalcite composite sol is prepared by the following method:
[0027] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:0.5, and ground to a particle size of 60 nm to obtain a nanopowder mixture.
[0028] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.1.
[0029] S3: slowly adding a nitric acid solution with a pH value of 2 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.5 mL:5 g, to obtain the binder of the present invention.
[0030] Example 2
[0031] According to the weight percentage, 99.8% of alumina (purity ≥ 99.99%, D50 = 0.3 μm) and 0.1% of sintering aid (Y2O3, particle size 180 nm) are weighed and prepared to obtain a mixture; the mixture: zirconium oxide ball: deionized water are added into a nylon ball mill according to the mass ratio of 1:4:1, and the mixture is mixed by planetary ball milling for 5 hours. After being taken out, the mixture is dried at 100°C and sieved with a 40-80 mesh sieve to obtain a powder; the obtained powder is added into a boehmite-hydrotalcite composite sol for granulation, the granules are placed into a molding mold and a green body is obtained at a pressure of 20 MPa; the obtained green body is placed into a sintering furnace for debinding at 600°C for 3 hours, and then sintered in an atmosphere at 1380°C for 8 hours to obtain 99 alumina ceramics.
[0032] In this embodiment, the boehmite-hydrotalcite composite sol is prepared by the following method:
[0033] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:0.5, and ground to a particle size of 60 nm to obtain a nanopowder mixture.
[0034] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.1.
[0035] S3: slowly adding a nitric acid solution with a pH value of 2 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.5 mL:5 g, to obtain the binder of the present invention.
[0036] Example 3
[0037] According to the weight percentage, 99.5% of alumina (purity ≥ 99.99%, D50 = 0.3 μm) and 0.07% of sintering aid (Y2O3, particle size 180 nm) are weighed and prepared to obtain a mixture; the mixture: zirconium oxide ball: deionized water are added into a nylon ball mill according to the mass ratio of 1:4:1, and the mixture is mixed by planetary ball milling for 3 hours. After being taken out, the mixture is dried at 90°C and sieved with a 40-80 mesh sieve to obtain a powder; the obtained powder is added into a boehmite-hydrotalcite composite sol for granulation, the granules are placed into a molding mold and a green body is obtained at a pressure of 30 MPa; the obtained green body is placed into a sintering furnace for debinding at 750°C for 3 hours, and then sintered in an atmosphere at 1450°C for 4 hours to obtain 99 alumina ceramics.
[0038] In this embodiment, the boehmite-hydrotalcite composite sol is prepared by the following method:
[0039] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:0.5, and ground to a particle size of 60 nm to obtain a nanopowder mixture.
[0040] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.1.
[0041] S3: slowly adding a nitric acid solution with a pH value of 2 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.5 mL:5 g, to obtain the binder of the present invention.
[0042] Example 4
[0043] According to weight percentage, 99.5% of alumina (purity ≥ 99.99%, D50 = 0.3 μm) and 0.05% of sintering aid (Y2O3, particle size 180 nm) are weighed and prepared to obtain a mixture; the mixture: zirconium oxide ball: deionized water are added into a nylon ball mill according to the mass ratio of 1:4:1, and the mixture is mixed by planetary ball milling for 6 hours. After being taken out, the mixture is dried at 80°C and sieved with a 40-80 mesh sieve to obtain a powder; the obtained powder is added into a boehmite-hydrotalcite composite sol for granulation, the granules are placed into a molding mold and a green body is obtained at a pressure of 30 MPa; the obtained green body is placed into a sintering furnace for debinding at 650°C for 3 hours, and then sintered in an atmosphere at 1450°C for 6 hours to obtain 99 alumina ceramics.
[0044] In this embodiment, the boehmite-hydrotalcite composite sol is prepared by the following method:
[0045] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:1, and ground to a particle size of 80 nm to obtain a nanopowder mixture.
[0046] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.3.
[0047] S3: slowly adding a nitric acid solution with a pH value of 3 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.8 mL:5 g, to obtain the binder of the present invention.
[0048] Example 5
[0049] According to weight percentage, 99.5% of alumina (purity ≥ 99.99%, D50 = 0.3 μm) and 0.05% of sintering aid (Y2O3, particle size 180 nm) are weighed and prepared to obtain a mixture; the mixture: zirconium oxide ball: deionized water are added into a nylon ball mill according to the mass ratio of 1:4:1, and the mixture is mixed by planetary ball milling for 6 hours. After being taken out, the mixture is dried at 80°C and sieved with a 40-80 mesh sieve to obtain a powder; the obtained powder is added into a boehmite-hydrotalcite composite sol for granulation, the granules are placed into a molding mold and a green body is obtained at a pressure of 30 MPa; the obtained green body is placed into a sintering furnace for debinding at 650°C for 3 hours, and then sintered in an atmosphere at 1450°C for 6 hours to obtain 99 alumina ceramics.
[0050] In this embodiment, the boehmite-hydrotalcite composite sol is prepared by the following method:
[0051] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:2, and ground to a particle size of 100 nm to obtain a nanopowder mixture.
[0052] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.5.
[0053] S3: slowly adding a nitric acid solution with a pH value of 3 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 1 mL:5 g, to obtain the binder of the present invention.
[0054] Comparative Example 1
[0055] According to the weight percentage, 99.5% of alumina (purity ≥ 99.99%, D50 = 0.3 μm) and 0.05% of sintering aid (Cr2O3, particle size of 180 nm) are weighed and prepared to obtain a mixture; the mixture: zirconium oxide ball: deionized water are added into a nylon ball mill according to the mass ratio of 1:4:1, and the mixture is mixed by planetary ball milling for 6 hours. After being taken out, the mixture is dried at 80°C and sieved with a 40-80 mesh sieve to obtain a powder; the obtained powder is added into a boehmite-hydrotalcite composite sol for granulation, the granules are placed into a molding mold and a green body is obtained at a pressure of 30 MPa; the obtained green body is placed into a sintering furnace for debinding at 650°C for 3 hours, and then sintered in an atmosphere at 1450°C for 6 hours to obtain 99 alumina ceramics.
[0056] In this embodiment, the boehmite-hydrotalcite composite sol is prepared by the following method:
[0057] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:1, and ground to a particle size of 80 nm to obtain a nanopowder mixture.
[0058] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.3.
[0059] S3: slowly adding a nitric acid solution with a pH value of 3 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.8 mL:5 g, to obtain the binder of the present invention.
[0060] Comparative Example 2
[0061] According to weight percentage, 99.5% of alumina (purity ≥ 99.99%, D50 = 0.3 μm) and 0.05% of sintering aid (Y2O3, particle size 180 nm) are weighed and prepared to obtain a mixture; the mixture: zirconium oxide ball: deionized water are added into a nylon ball mill according to the mass ratio of 1:4:1, and the mixture is mixed by planetary ball milling for 6 hours. After being taken out, the mixture is dried at 80°C and sieved with a 40-80 mesh sieve to obtain a powder; the obtained powder is added into a boehmite-hydrotalcite composite sol for granulation, the granules are placed into a molding mold and a green body is obtained at a pressure of 30 MPa; the obtained green body is placed into a sintering furnace for debinding at 650°C for 3 hours, and then sintered in an atmosphere at 1450°C for 6 hours to obtain 99 alumina ceramics.
[0062] In this embodiment, the boehmite sol is prepared by the following method:
[0063] S1: Grind boehmite to a particle size of 80 nm to obtain a nanopowder mixture.
[0064] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.3.
[0065] S3: slowly adding a nitric acid solution with a pH value of 3 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.8 mL:5 g, to obtain the binder of the present invention.
[0066] Comparative Example 3
[0067] According to weight percentage, 99.5% of alumina (purity ≥ 99.99%, D50 = 0.3 μm) and 0.05% of sintering aid (Y2O3, particle size 180 nm) are weighed and prepared to obtain a mixture; the mixture: zirconium oxide ball: deionized water are added into a nylon ball mill according to the mass ratio of 1:4:1, and the mixture is mixed by planetary ball milling for 6 hours. After being taken out, the mixture is dried at 80°C and sieved with a 40-80 mesh sieve to obtain a powder; the obtained powder is added into a boehmite-hydrotalcite composite sol for granulation, the granules are placed into a molding mold and a green body is obtained at a pressure of 30 MPa; the obtained green body is placed into a sintering furnace for debinding at 650°C for 3 hours, and then sintered in an atmosphere at 1450°C for 6 hours to obtain 99 alumina ceramics.
[0068] In this embodiment, the hydrotalcite sol is prepared by the following method:
[0069] S1: Grind the hydrotalcite to a particle size of 80 nm to obtain a nanopowder mixture.
[0070] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.3.
[0071] S3: slowly adding a nitric acid solution with a pH value of 3 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.8 mL:5 g, to obtain the binder of the present invention.
[0072] Performance Characterization of 99 Alumina Ceramics Prepared in Examples and Comparative Examples
[0073] Micro Vickers hardness test: The test standard is GB / T16534-2009 Fine Ceramics Room Temperature Hardness Test Method, the room temperature is about 20℃, a 40x objective lens is used, the load is HV0.5 (4.903N), the holding time is 10 seconds, and the bending strength is tested by a universal tensile testing machine for three-point bending strength of ceramics (sample size 3mm×4mm×35mm, 10 samples are measured in each group to take the average value): The breakdown voltage is tested by HCDJC-100kV voltage breakdown tester, and the specific results are as follows:
[0074]
[0075]
[0076] Comparing the above-mentioned Examples 1-5 and Comparative Examples 2-3, it can be seen that the present invention uses boehmite and hydrotalcite as the main components of the binder, and combines a specific preparation method to obtain the binder, which is applied to the preparation process of alumina ceramics, and can avoid the disadvantage that the alumina ceramics have pores and cracks due to the decomposition and overflow of the traditional binder under high temperature conditions, thereby improving the compactness of the alumina ceramics, and improving the strength and hardness of the alumina ceramics. The MgO produced by the calcination of hydrotalcite in the binder of the present invention can significantly reduce the temperature of the conversion to α-Al2O3 during the sintering process of boehmite and alumina, and thus can reduce the calcination temperature of alumina ceramics, that is, the present invention can obtain a high-density alumina ceramic product by calcining at a relatively low temperature. The binder used in the present invention plays the role of a binder in the early stage of the sintering process, thereby reducing the pores and cracks caused by the excessive use of organic binders during the sintering process. The magnesium aluminum spinel and magnesium oxide produced by the hydrotalcite during the sintering process can play the role of a sintering aid, thereby reducing the amount of sintering aids added.
[0077] By comparing Example 4 with Comparative Example 1, it can be seen that the present invention uses Y2O3 as a sintering aid, which can react with MgO and Al2O3 produced by decomposition in the binder to generate a low-melting-point liquid phase, which helps to redistribute the material between the particles and fill the pores, further improving the density and enhancing the dielectric properties.
Claims
1. A high strength 99 alumina ceramic, characterized in that The invention comprises the following components by mass percentage: 99.5-99.8% of aluminum oxide, 0.05-0.1% of sintering aid, and the balance of boehmite-hydrotalcite composite sol.
2. A high strength 99 alumina ceramic as claimed in claim 1, characterized in that: The purity of the aluminum oxide is ≥99.99%, and D50=0.3 μm.
3. A high strength 99 alumina ceramic as claimed in claim 1, characterized in that: The sintering aid is one of Cr2O3 and Y2O3, and the particle size is 180-200nm.
4. A high strength 99 alumina ceramic as claimed in claim 1, characterized in that: The boehmite-hydrotalcite composite sol is prepared by the following method: S1: mixing boehmite and hydrotalcite in a mass ratio of 1:0.5-2, and grinding to a particle size of 60-100 nm to obtain a nanopowder mixture; S2: adding the ground nanopowder mixture to the dispersant and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.1-0.5; S3: slowly adding a nitric acid solution with a pH value of 2-3 to the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.5-1 mL:5 g, to obtain a boehmite-hydrotalcite composite sol.
5. A high strength 99 alumina ceramic as claimed in claim 4, characterized in that: In step S1, the particle size of boehmite and hydrotalcite before grinding is 180-200 nm.
6. A high strength 99 alumina ceramic as claimed in claim 4, characterized in that: The dispersant in step S2 is polyvinyl alcohol.
7. A method for preparing the high-strength 99 alumina ceramic according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: weigh alumina and sintering aid according to the above ratio, mix the ingredients to obtain a mixture; ball mill, and sieve to obtain powder; Step 2: adding the powder obtained in step 1 to the boehmite-hydrotalcite composite sol to granulate, and placing the granules into a molding mold to press to obtain a green body; Step 3: Place the green body obtained in step 2 into a sintering furnace for debinding at 600-750°C for 3 hours, and then sinter at 1380-1450°C in an atmosphere for 4-8 hours to produce 99 alumina ceramics.
8. A method for preparing the high-strength 99 alumina ceramic according to any one of claims 1 to 6 according to claim 7, characterized in that: The specific conditions of ball milling in step 1 are: adding the mixture: zirconium oxide balls: deionized water in a mass ratio of 1:4:1 into a ball mill, ball milling and mixing for 3-6 hours, taking out and drying at 80-100° C., and sieving with a 40-80 mesh sieve to obtain a powder.
9. A method for preparing the high-strength 99 alumina ceramic according to any one of claims 1 to 6 as claimed in claim 7, characterized in that: The pressing pressure in step 2 is 10-30 MPa.
10. Application of the high-strength 99 alumina ceramics according to any one of claims 1 to 6 in high-frequency insulating materials.
Citation Information
Patent Citations
Production process of high-hardness aluminum oxide ceramic
CN117923887A
Cited By
Low-temperature sintering preparation process of aluminum oxide ceramic doped with composite additive
CN122212694A